Crystallographic studies on the binding of isonicotinyl-NAD adduct to wild-type and isoniazid resistant 2-trans-enoyl-ACP (CoA) reductase from Mycobacterium tuberculosis - Dias, Marcio Vinicius Bertacine; Vasconcelos, Igor Bordin; Prado, Adriane Michele Xavier; Fadel, Valmir; Basso, Luiz Augusto; De Azevedo, Walter Filgueira; Santos, Diogenes Santiago (Elsevier B.V., 2007)
The resumption of tuberculosis led to an increased need to understand the molecular mechanisms of drug action and drug resistance, which should provide significant insight into the development of newer compounds. Isoniazid (INH), the most prescribed drug to treat TB, inhibits an NADH-dependent enoyl-acyl carrier protein reductase (InhA) that provides precursors of mycolic acids, which are components of the mycobacterial cell wall. InhA is the major target of the mode of action of isoniazid. INH is a pro-drug that needs activation to form the inhibitory INH-NAD adduct. Missense mutations in the inhA structural gene have been identified in clinical isolates of Mycobacterium tuberculosis resistant to INH. To understand the mechanism of resistance to INH, we have solved the structure of two InhA mutants (121V and S94A), identified in INH-resistant clinical isolates, and compare them to INH-sensitive WT InhA structure in complex with the INH-NAD adduct. We also solved the structure of unliganded INH-resistant S94A protein, which is the first report on apo form of InhA. The salient features of these structures are discussed and should provide structural information to improve our understanding of the mechanism of action of, and resistance to, INH in M. tuberculosis. The unliganded structure of InhA allows identification of conformational changes upon ligand binding and should help structure-based drug design of more potent antimycobacterial agents. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Mycobacterium tuberculosis; InhA; Crystal structure; isoniazid; drug resistance; Enoyl-ACP reductase